Recent trend on Tetradenia riparia (Hochst.) Codd (Lamiaceae) for management of medical conditions - Amos Luanda; Asha Ripanda (Elsevier, 2023)
Background: Tetradenia riparia (Hochst.) Codd (Lamiaceae) is a medicinal plant traditionally utilized to manage various transmitted and non-transmitted diseases such as HIV/AIDS, malaria, respiratory problems and diabetes. All parts of this plant have been utilized and demonstrated a positive promise for managing medical conditions. Several studies have been conducted to evaluate its pharmacological potentials, such as antibacterial, anthelmintic, larvicidal, antifungal, antileishmanial, antioxidant and insecticidal activities. Purpose: This review aims to address the potential of T. riparia for managing medical conditions, challenges and future research directions. In particular, the bioactive compounds responsible for pharmacological properties are discussed. Study design: The well-explained relevant studies and the most appropriate studies based on the selected topic were chosen. The obtained information was analyzed to determine the outcome by screening sources by title, abstract, and whole work. The selected studies were chosen in an agreement between the authors. The relevant information was sorted systematically into titles and subtitles and compressively discussed. Methods: The information presented in this review is obtained from various online platforms such as Google scholar, Springer, ScienceDirect, Web of Science and PubMed by searching using specific terms and phrases. The selected works based on the inclusion criteria as agreed by all authors. Results: The phytochemical profile of T. riparia revealed the presence of several phytoconstituents, which support the pharmacological potentials of the plant. Findings revealed that both T. riparia essential oil and extracts have significant medicinal potentials remarkable for mitigating medical conditions, but the former outperforms the latter in terms of pharmacological potentials. Additionally, T. riparia has potential prospects in major medical conditions like tuberculosis, diabetes, malaria, snake bites, gonorrhea, dental abscesses, gastroenteritis, diarrhoea, etc. Conclusion: This study revealed that Tetradenia riparia is a promising medicinal plant that can be employed as an alternative medicine against various medical conditions.